Tes Dianostik Two Tier untuk mengidentifikasi Miskonsepsi pada pelajaran IPAS materi Tumbuhan di SDN Sonosewu - Prastyani, Oktina Dwi; Kurniawati, Wahyu (Borobudur Educational Review, 2025)
Science learning in elementary school means that students can understand concepts. However, some students find it difficult to understand the concept of science learning. One of the causes of students' inability to understand concepts is when students experience misconceptions. The presentation of misconceptions on the topic "Parts of plants" in class IV A was 57.7% of 26 students and in Class IV B 55.6% of 18 students. The results from both classes are included in the percentage in the "Medium" category. Then in the Topic "Photosynthesis" IV A 61.5% of 26 students and Class IV B 61.1% of 18 students. The percentage results show that both classes are in the "High" category. Then on the topic "Plant reproduction" 53.8% of 26 students were in the "Medium" category and Class IV B 66.7% of 18 students were in the "High" category. And the following are the misconception factors among class IV students at Sonosewu Elementary School, namely 1). Preconceptions at the beginning of learning, 2). Differences between students in receiving the material that the teacher has conveyed, 3). Lack of direct practice during learning.